Protective effect of Korean red ginseng water extract on levothyroxine-induced hyperthyroidism and propylthiouracil-induced hypothyroidism in rats - Lei Huang; Won Young Jang; Ji Hye Yoon; Zhenyan Piao; Jinghan Su; Dong Seon Kim; Ki Woong Kwon; Ji Won Kim; Sang Hee Park; Sunggyu Kim; Jong-Hoon Kim; Jae Youl Cho (Integrative Medicine Research, 2024)
Background: Korean red ginseng extract (KRGE) (Family: Araliaceae) is one of the most widely used traditional herbs in Asia. Multiple studies have shown that KRGE has anti-inflammation, anti-fatigue, anti-obesity, anti-oxidant, and anti-cancer effects. Methods: Sprague-Dawley rats were divided into five groups for PTU-induced hypothyroidism and six groups for LT4-induced hyperthyroidism. At the experiment's conclusion, rats were sacrificed, and blood, thyroid gland, and liver samples were collected. Body weight was recorded weekly, and serum hormone levels were assessed using enzyme-linked immunoassay. Thyroid gland and liver tissues were stained with hematoxylin and eosin. KRGE was prepared in 0.5% CMC and stored at 4 °C before administration. Results: In the LT4-induced hyperthyroidism model, KRGE prevented decreases in body weight, thyroid gland weight, liver weight, serum glucose, and thyroid hormone levels compared to the PTU group. It also reduced increases in T3, T4, and serum aspartate aminotransferase levels after LT4 treatment. Additionally, KRGE improved thyroid gland and liver histopathology, effects not observed in the PTU-induced hypothyroidism model. Conclusion: All things considered, our research points to KRGE's potential protective role in rat hyperthyroidism caused by LT4 by lowering thyroid hormone production.